SINERGITAS KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI BENGKULU DAN BADAN AMIL ZAKAT NASIONAL PROVINSI BENGKULU DALAM PENGELOLAAN ZAKAT - Anggraini, Wiwit (UIN Fatmawati Sukarno Bengkulu, 2018)
The formulation of this research are: First, how the management of zakat at Badan Amil Zakat Nasional (BAZNAS) of Bengkulu Province? Second, what is the role of the Regional Office of the Ministry of Religious Affairs of Bengkulu Province in the management of zakat at the National Amil Zakat Agency of Bengkulu Province? Third, how is the synergy between the Regional Office of the Ministry of Religious Affairs of Bengkulu Province and BAZNAS of Bengkulu Province in the manage- ment of zakat? The research method used is evaluative method.The study concluded that: first of zakat management at the National Zakat Agency Bengkulu province include charity fund rais- ing, distribution and utilization of zakat. Second, the role of the Regional Office of the Ministry of Religious Bengkulu province in Zakat Management Agency National Zakat Bengkulu province is the founder, partner, facilitator, coordinator and motivator for the management of zakat that is professional and trustworthy, strive to increase the role of zakat to be a professional institution, transparent trusts and guidance to the empowerment of zakat functionally includes preparation of the materials empowerment of zakat, preparation of materials institutional accreditation zakat, preparation of materials certification institutional charity, management Unit Gatherer zakat and collect data with regard to the management of zakat on Unit Gatherer zakat in the Office of Religious Affairs Regency / City. Third, form synergy in zakat management is Unit Gatherer Zakat Regional Office of the Ministry of Religious Bengkulu Province has been collecting zakat, infaq and sadaqah from across the Civil Service through a system of payroll deductions, held activities in cooperation with the National Zakat Bengkulu province, conducting monitoring activities zakat fund management at the national zakat Agency se City District of Bengkulu province, Amil zakat Development of technical guidance and assistance Operational national zakat Agency in accordance with the province and the availability of funds each year